Effect of Saccadic Adaptation on Sequences of Saccades - Muriel Panouillères; Roméo Salemme; Christian Urquizar; Denis Pélisson (Bern Open Publishing, 2012)
Accuracy of saccadic eye movements is maintained thanks to adaptation mechanisms. The adaptive lengthening and shortening of reactive and voluntary saccades rely on partially separate neural substrates. Although in daily-life we mostly perform sequences of saccades, the effect of saccadic adaptation has been mainly evaluated on single saccades. Here, sequences of two saccades were recorded before and after adaptation of rightward saccades. In 4 separate sessions, reactive and voluntary saccades were adaptively shortened or lengthened. We found that the second saccade of the sequence always remained accurate and compensated for the adaptive changes of the first rightward saccade size. This finding suggests that adaptation loci are upstream of the site where the efference copy involved in sequence planning originates.